2014
DOI: 10.1371/journal.pone.0100402
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Pilates Exercise in People with Chronic Low Back Pain: A Systematic Review

Abstract: ObjectiveTo evaluate the effectiveness of Pilates exercise in people with chronic low back pain (CLBP) through a systematic review of randomised controlled trials (RCTs).Data SourcesA search for RCTs was undertaken using Medical Search Terms and synonyms for “Pilates” and “low back pain” within the maximal date range of 10 databases. Databases included the Cumulative Index to Nursing and Allied Health Literature; Cochrane Library; Medline; Physiotherapy Evidence Database; ProQuest: Health and Medical Complete,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
85
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 42 publications
(199 reference statements)
3
85
0
14
Order By: Relevance
“…Created by Joseph Pilates in the 1920s, Pilates blends Western yoga, Greek and Roman gymnastics, karate, and Zen, among others, and has developed into a series of physical and mental conditioning exercises. It is arguable whether Pilates reduces back pain and enhances the functional capabilities of nonspecific CLBP patients13,14,15,16,17,18 ) . Some systematic reviews have shown that when compared with a placebo or normal daily activities, Pilates relieves pain but does not reduce disability13, 14 ) , while others have shown that Pilates does not reduce disabilities and/or pain15 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Created by Joseph Pilates in the 1920s, Pilates blends Western yoga, Greek and Roman gymnastics, karate, and Zen, among others, and has developed into a series of physical and mental conditioning exercises. It is arguable whether Pilates reduces back pain and enhances the functional capabilities of nonspecific CLBP patients13,14,15,16,17,18 ) . Some systematic reviews have shown that when compared with a placebo or normal daily activities, Pilates relieves pain but does not reduce disability13, 14 ) , while others have shown that Pilates does not reduce disabilities and/or pain15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Some systematic reviews have shown that when compared with a placebo or normal daily activities, Pilates relieves pain but does not reduce disability13, 14 ) , while others have shown that Pilates does not reduce disabilities and/or pain15 ) . Still others have shown that when compared with a placebo or normal daily activities, Pilates may effectively relieve pain and reduce the degree of disability18 ) . However, in several other systematic reviews, Pilates showed no significant differences compared with any other form of exercise14, 15, 18 ) ; in another review, Pilates effectively reduced disabilities compared with others forms of exercise13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Techniques which provide improved lumbar-pelvic stability, such as the Pilates method, can be considered in cases where the patient presents a stable framework (Oliveira et al, 2013;Wells et al, 2014). The method enables improvement in muscle strength and range of motion in this region (Natour et al, 2014;Wells et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with a similar intervention period (12 weeks) also found improvement in the strength of active muscles in that region of the after intervention with the Pilates method.Kao et al (2014) observed that this period of training can significantly modify muscle strength in this region.Emery et al (2010), also found modification in muscle strength of the trunk flexors, and the study of Kloubec (2010) observed significant improvement in both the flexor and extensor trunk muscles, in a 12-week intervention.The muscles that perform flexion and extension of the trunk are fundamental to lumbar-pelvic stability(Lee et al, 2014;Wells et al, 2014), and strengthening these muscles is essential in the treatment of disorders related to the spine, such as spondylolisthesis(Oliveira et al, 2013). Pilates exercises, seeking to increase strength in the spine stabilizers, have been related to a decrease in the incidence of new lesions and improvement in the level of pain and functionality Natour et al, 2014; Oliveira 2013).In the present study, an improvement in muscle strength of the knee flexors and extensors was also observed, represented by the peak isokinetic torque, both at a lower angular velocity (60°/s) and a higher angular velocity (300°/s ); exceeding 50% improvement inboth variables.…”
mentioning
confidence: 99%
“…Os exercícios podem ser executados no solo sem uso de aparelhos (Mat Pilates), ou envolver o uso de equipamentos especializados que oferecem resistência ajustável. O método Pilates pode ser indicado para qualquer indivíduo, de diferentes faixas etárias, sendo mais frequentemente prescrito para pessoas com dor lombar crônica, para correção postural e melhora do equilíbrio dinâmico, da flexibilidade, da força e da resistência, para o aumento da massa muscular e redução de massa gorda, para reabilitação e para a melhoria da qualidade de vida [17,18].…”
Section: Introductionunclassified